Determinants of pulse pressure and annual rates of change in the Atherosclerosis Risk in Communities study. Issue 12 (December 2015) - Butler, Kenneth R.; Penman, Alan D.; Minor, Deborah S.; Mosley, Thomas H.
Abstract : Introduction: The aim of this study was to examine the effect of vascular and lifestyle risk factors on the annual rate of change in pulse pressure (PP) in a biracial, middle-aged cohort. Methods and results: The study population, drawn from the Atherosclerosis Risk in Communities (ARIC) cohort, included 10 071 participants, aged 45–64 years at baseline, with a complete set of SBP and DBP readings at each of four visits 3 years apart. The average annual increase in PP was 1.23 mmHg [standard error (SE 0.01], after adjusting for baseline age differences. Compared with white men, African-American women had the highest rate of annual increase in PP (0.41 (SE 0.05) mmHg/year greater) followed by white women [0.23 (SE 0.03) mmHg/year greater] and African-American men [0.19 (SE 0.06) mmHg/year greater]. Conclusion: There were significant differences in both average baseline PP and average annual rate of change in PP between men and women and African-Americans and whites. Diabetes and obesity had the strongest effect on the absolute value of baseline PP and the annual rate of change in PP.